2001
DOI: 10.1128/mcb.21.8.2755-2766.2001
|View full text |Cite
|
Sign up to set email alerts
|

S and G2 Phase Roles for Cdk2 Revealed by Inducible Expression of a Dominant-Negative Mutant in Human Cells

Abstract: Cyclin-dependent kinase 2 (Cdk2) is essential for initiation of DNA synthesis in higher eukaryotes. Biochemical studies in Xenopus egg extracts and microinjection studies in human cells have suggested an additional function for Cdk2 in activation of Cdk1 and entry into mitosis. To further examine the role of Cdk2 in human cells, we generated stable clones with inducible expression of wild-type and dominant-negative forms of the enzyme (Cdk2-wt and Cdk2-dn, respectively). Both exogenous proteins associated effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
133
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(149 citation statements)
references
References 75 publications
11
133
2
1
Order By: Relevance
“…A number of laboratories have provided evidence that G 2 phase cyclin A/cdk2 has a critical role in the timing of entry into mitosis (Furuno et al, 1999;Goldstone et al, 2001;Hu et al, 2001;Mitra and Enders, 2004;Fung et al, 2007;Gong et al, 2007), which is confirmed by our siRNA and cdk2-specific inhibitor studies. In agreement with these reports, the present study demonstrates that inhibition of G 2 phase cyclin A/cdk2 delays the cdc25-dependent activation (Mitra and Enders, 2004;Fung et al, 2007), and nuclear translocation (Gong et al, 2007) of cyclin B/cdk1.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A number of laboratories have provided evidence that G 2 phase cyclin A/cdk2 has a critical role in the timing of entry into mitosis (Furuno et al, 1999;Goldstone et al, 2001;Hu et al, 2001;Mitra and Enders, 2004;Fung et al, 2007;Gong et al, 2007), which is confirmed by our siRNA and cdk2-specific inhibitor studies. In agreement with these reports, the present study demonstrates that inhibition of G 2 phase cyclin A/cdk2 delays the cdc25-dependent activation (Mitra and Enders, 2004;Fung et al, 2007), and nuclear translocation (Gong et al, 2007) of cyclin B/cdk1.…”
Section: Discussionsupporting
confidence: 83%
“…The previous studies examining the mechanism by which depletion of G 2 phase cyclin A/cdk2 regulates progression into mitosis have provided evidence for deregulation of Wee1 activity (Fung et al, 2007) and cytoplasmic retention of cyclin B1 (Gong et al, 2007). The mechanism appears independent of ataxia telangiectasia mutated/ATM and Rad3 related (ATM/ATR) checkpoint signalling (Hu et al, 2001;Fung et al, 2007). The mechanism by which cyclin A/cdk2 coordinates activation of the centrosomal and soluble pools is also unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that JNK1/2-dependent signals may play important roles in the platonin-mediated inhibition of VSMC proliferation. Furthermore, JNK, c-Jun, and p27 activation have also been reported to regulate S and G 2 /M phases of cell-cycle progression [28][29][30][31] . These studies are consistent with our finding that the platonin treatment arrested cell cycle progression in the S and G 2 /M phases, which may have resulted from the suppression of JNK1/2-dependent signals.…”
Section: Discussionmentioning
confidence: 99%
“…In the human OSA cell line U-2OS, combined depletion of CDK1 and CDK2 but not anyone alone by RNA silencing has been proved to arrest cells in G2-M phase and to induce apoptosis (Hu et al, 2001;Cai et al, 2006;Wei et al, 2011).…”
Section: Cdks Play An Import Role In the Pathogenesis Of The Osamentioning
confidence: 99%